The impact of an individual tutorial session on MEDLINE use among obstetrics and gynaecology residents in an academic training programme: a randomized trial. - Erickson S; Warner ER (Medical Education, 1998)
Over the past decade, on-line databases have become increasingly popular among health care professionals. As a group, these 'end-users' report utilizing databases to keep abreast of medical progress, to conduct research and to address specific patient care issues. Throughout the literature, medical professionals ('content experts') have proved to be less effective searchers than librarians ('search experts'). The potential implications of this discrepancy are worrysome. For any given clinical scenario, for example, published reports may reach contradictory conclusions. A poorly skilled searcher may not retrieve enough articles to appreciate this fact. Optimizing searching skills is therefore a worthwhile goal. As a first step, many medical schools introduce students to on-line databases, most notably MEDLINE. Residency is an ideal time to continue this training. A recognized obstacle to provide residents with formal MEDLINE instruction is time constraint. We therefore conducted this study to ascertain the impact an individual 1-hour tutorial session would have on MEDLINE utilization among obstetrics and gynecology residents training at an academic medical centre. Outcome measures included MEDLINE search frequency, duration, recall, precision and searcher satisfaction. Search recall measures the searcher's ability to retrieve articles deemed relevant to the question at hand. Search precision gauges the searchers' ability to eliminate irrelevant articles. Although the sessions were well received, we were unable to demonstrate an improvement in the outcome measures analysed. Further research is therefore indicated so that cost-effective educational strategies can be recommended for wide-scale use.